Multidisciplinary clinic for care of children with complex obstructive sleep apnea. (November 2020) - DeVries, Jacquelyn K.; Nation, Javan J.; Nardone, Zachary B.; Lance, Samuel H.; Stauffer, Jacy A.; Abichaker, George M.; Bhattacharjee, Rakesh; Lesser, Daniel J.
Abstract: Objective: While adenotonsillectomy (AT) remains first line therapy for pediatric obstructive sleep apnea (OSA), management of children who are not candidates for AT or who have residual OSA post AT varies and spans across multiple specialties. We aim to report our experience in managing this population through a multidisciplinary sleep clinic composed of specialists in pediatric dentistry, otolaryngology, plastic surgery, and pulmonary/sleep medicine. Study design: Retrospective chart review. Method: The medical records of children attending our complex sleep apnea clinic were reviewed. Data pertaining to demographics, underlying diagnoses, prior evaluation and treatment, recommendations, and initial therapy were collected. Result: Two-hundred and thirty patients (mean age 10.7 ± 5.1 years, 62.2% male) were assessed. Underlying conditions included Trisomy 21 (n = 65, 28.2%), other genetic syndromes (n = 37, 16.1%), obesity in an otherwise typically developing child (n = 36, 15.2%), cerebral palsy (n = 27, 11.7%), and craniofacial syndromes (n = 7, 3.0%). Mean obstructive apnea hypopnea index (OAHI) was 14.2 events/hour at first clinic visit, and the majority of children had previously undergone at least one upper airway surgery (n = 168, 73.0%), primarily adenotonsillectomy. Recommended initial treatment plans included positive airway pressure (PAP) therapy (n = 108, 47.0%), surgery (n = 75, 32.6%), allergy management (n = 52, 22.6%), and/or weight loss (n = 34, 14.8%). Patients prescribed PAP therapy with follow up data were found to be adherent 43.9% of the time. Surgical patients with post-operative polysomnography had pre-operative OAHI 15.6 ± SD13.4 decrease to 10.7 ± 14.2 events/hour (p = 0.61). Conclusion: Genetic conditions and obesity were the most common underlying diagnoses cared for in the complex sleep apnea clinic. Patients presented with severe OSA, most having already had upper airway surgery. Management plans were frequently adjusted, and we observed improvement in SDB in a sub-segment of patients, suggesting benefit to a coordinated, multi-disciplinary approach.